Information Security Theory and Practice : 12th IFIP WG 11.2 International Conference, WISTP 2018, Brussels, Belgium, December 10-11, 2018, Revised Selected Papers /: 12th IFIP WG 11.2 International Conference, WISTP 2018, Brussels, Belgium, December 10-11, 2018, Revised Selected Papers. (2019) - Unknown
No abstract available